Intranet Meets Hospital Information Systems: The Solution to the Integration Problem? - Lenz, R.; Kuhn, K. A. (Methods of Information in Medicine, 2001)
Based on the results of an extensive market analysis and technology assessment, this paper summarizes the state of the art in web technology and compares it with the needs of integration in hospital information systems. Web technology and intranet have evolved to a core technology for distributed computing and distributed information systems. The advantage of platform independent distribution of information has led to euphoric visions of future integrated systems. However, true integration takes more than transparent access to heterogeneous information sources. To overcome the essential problems related to integration of autonomous systems it is important to find a common ontological basis for future component based systems.
Keywords: Internet; Hospital Information Systems; Systems Integration